Heats of formation and stress–strain relationship of Fe–Cr solid solutions from a constructed Fe–Cr potential. (1st June 2022) - Peng, D K; Jiang, Y C; Gong, H R; Liang, C P
Abstract: A new Fe–Cr interatomic potential is constructed under the framework of the embedded-atom method and has better performances in predicting heats of formation and stress–strain relationship of Fe–Cr solid solutions than the Fe–Cr potentials already published in the literature. Based on the constructed Fe–Cr potential, molecular dynamics simulation reveals that the heats of formation of BCC Fe–Cr solid solutions at 1600 K are positive within the entire composition range, and the calculated values are in good agreement with corresponding experimental measurements in the literature. In addition, it is also found that the tensile strengths of BCC Fe–Cr solid solutions increase with the increase of the Cr composition, and that BCC Fe–Cr solid solutions are less ductile with smaller critical strains than both Fe and Cr. The simulated results are discussed and compared with the corresponding experimental and calculated evidence in the literature to validate the relevance of the newly constructed Fe–Cr potential.